2016
DOI: 10.1177/1550147716659424
|View full text |Cite
|
Sign up to set email alerts
|

A rapid joining scheme based on fuzzy logic for highly dynamic IEEE 802.15.4e time-slotted channel hopping networks

Abstract: The IEEE 802.15.4e standard is an amendment of the IEEE 802.15.4-2011 protocol by introducing time-slotted channel hopping access behavior mode. However, the IEEE 802.15.4e only defines time-slotted channel hopping link-layer mechanisms without an investigation of network formation and communication scheduling which are still open issues to the research community. This article investigates the network formation issue of the IEEE 802.15.4e time-slotted channel hopping networks. In time-slotted channel hopping n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…Moreover, we compare our model with [8] since they considered the decentralized network; it is observed that AS technique achieves the satisfactory trade-off between energy overhead and routing performance. Hence from discussion it is clear that our model outperforms the various state-of-art technique [8], [10], [11], [12], [13], and [14] considering the carious parameter such as access fairness, packet delivery rate and energy overhead.…”
Section: Comparision With Existing Modelmentioning
confidence: 87%
See 2 more Smart Citations
“…Moreover, we compare our model with [8] since they considered the decentralized network; it is observed that AS technique achieves the satisfactory trade-off between energy overhead and routing performance. Hence from discussion it is clear that our model outperforms the various state-of-art technique [8], [10], [11], [12], [13], and [14] considering the carious parameter such as access fairness, packet delivery rate and energy overhead.…”
Section: Comparision With Existing Modelmentioning
confidence: 87%
“… The main advantage of Adaptive Scheduling is that it provisions for the high traffic application and this does not have any effect on the energy consumption of MANET, furthermore this is achieved through activating the additional slots dynamically and it does not require the reorganizing of new schedule.  The Adaptive model outperforms various state-of-art technique such as [8], [10], [11], [12], [13] and [14] in terms of access fairness, packet transmission and energy efficiency.…”
Section: The Contribution Of Work Is As Followsmentioning
confidence: 94%
See 1 more Smart Citation
“…Duy et al [6]. divided slotframe into advertisement plane and communication plane to avoid the EB collisions in congested situations.…”
Section: Related Workmentioning
confidence: 99%
“…As the number of slots used to transmit EBs in the entire Timeslot is smaller, the number of slots to which data can be transmitted is increased, and the data rate of the entire network is increased. In this experiment, Rapid [6], a comparison algorithm, compares our algorithm with the technique of changing the number of EBs according to neighbor nodes. The experiment was divided into 5 nodes and 20 nodes.…”
Section: Comparison Of the Proportion Of Eb Slots In The Total Numbermentioning
confidence: 99%